2023
DOI: 10.54187/jnrs.1219721
|View full text |Cite
|
Sign up to set email alerts
|

Mersenne version of Brocard-Ramanujan equation

Abstract: In this study, we deal with a special form of the Brocard-Ramanujan equation, which is one of the interesting and still open problems of Diophantine analysis. We search for the positive integer solutions of the Brocard-Ramanujan equation for the case where the right-hand side is Mersenne numbers. By using the definition of Mersenne numbers, appropriate inequalities for the parameters of the equation, and the prime factorization of $n!$ we show that there is no positive integer solution to this equation. Thus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…which later became known as the Brocard-Ramanujan Diophantine equation. The only known solutions of (1) are (4,5), (5,11) and (7,71). It is claimed in [4] that equation (1) cannot have solutions when n!…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which later became known as the Brocard-Ramanujan Diophantine equation. The only known solutions of (1) are (4,5), (5,11) and (7,71). It is claimed in [4] that equation (1) cannot have solutions when n!…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was shown that there do not exist positive integers m and n that satisfy equation (2). For more versions of Brocard-Ramanujan Diophantine equation, see in [6,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%